Enhancing Supply Chain Agility and Performance through Electronic Procurement: A Study of the Palestinian Industrial Sector (The International Journal for Scientific Research, 2024)
Objective: The study aimed to explore the direct impact of e-procurement on the agility and performance of the supply chain in the Palestinian industrial sector.Methodology: The questionnaire was used as the main tool for the study. It contained a set of questions to measure the study variables. It was designed based on previous studies. This study was conducted on a sample of 288 individuals from the owners of companies in the Palestinian industrial sector, their managers and decision-makers. A number of hypotheses were formulated and examined using the structural equation model (Structural Equation Modeling (SEM), using the statistical program SmartPls4. Results: The study found a positive significant impact of e-procurement in its combined dimensions (e-design, e-sources, e-negotiation, and e-evaluation) on the agility of the supply chain. As for the results of the impact of the individual dimensions of e-procurement, the study found a positive significant impact for all dimensions except the dimension of e-negotiation on the agility of the supply chain. The study also found a positive significant impact for both e-procurement and supply chain agility on its performance. Conclusion: E-procurement is an important tool in enhancing the agility of the supply chain in the industrial sector, and an important factor in improving the performance of this chain.
Keywords: E-procurement; Supply chain agility; Supply chain performance; Palestine